Fabrication And Characterisation Of Mono- And Multifilament Ag-Sheathed Bi₁.₆Pb₀.₄Sr₂Ca₂Cu₃O₁₀ Superconductor Tapes Via Powder-Wire-In-Tube Technique - Ahmad, Masrianis (2005)
The co-precipitation technique was used in the preparation of Bi₁.₆Pb₀.₄Sr₂Ca₂Cu₃O₁₀ polycrystalline ceramic superconductor powder to fabricate Ag-sheathed superconductor tapes. Powder prepared via co-precipitation method with ultra-fine grain size was used to enhance the Bi-2223 phase formation. The tapes were prepared using the powder-in-tube and powder-wire-in-tube method. The powderwire- in-tube (PWIT) method has been developed by packing powder together with composite wires into silver tubes at the second stage of the powder-in-tube (PIT) process. Among the different routes proposed to enhance Bi-2223 phase formation, the PWIT method showed better results. The samples were prepared with different number of filaments (number of filament = 2, 4, 6, 8; PWIT and 0, 20; PIT) and different sintering times (24 hr, 48 hr and 100 hr) heated at 850˚C. Samples heated for longer time showed enhanced 2223 phase formation for pellet and monofilament tape samples from 92% to 96% and 84% to 86% respectively. The intergranular connectivity can be improved. Sintering temperature 850˚ enhanced the growth of the superconductor phase, which was much faster in the ab-plane than along the c-axis.This made the platelets form well-aligned connections with each other. in the Bi-2223 XRD peak intensity with sintering time is due to the re-arrangement of the Bi-2212 crystals, which occurs in the larger volume of liquid phase. A slight preferred orientation of the grains in the c-axis direction when the samples were rolled into tapes was also observed. By increasing the sintering time the average grain size is increase from 4 µm to 14 µm and by increasing the number of filaments from 2 to 8 filaments inside the tube and core area that developed the nonsuperconducting phase and the secondary phase were minimized. Small filaments in multifilament tapes are more homogenous than monofilament tapes owing to the better grain orientation along the silver sheath. At 77 K and zero field, the highest transport critical current density (Jc) 11500 ± 300 A/cm² was achieved in the tape prepared via PWIT (number of filament = 8) sintered for 1 00 hours compared to PIT method with transport critical current density (Jc) 7800 ± 300 A/cm² at the same sintering duration. Therefore, critical current density increases with the sintering duration and number of filaments.